Effects of Exercise Training Combined with Increased Physical Activity to Prevent Chronic Pain in Community-Dwelling Older Adults: A Preliminary Randomized Controlled Trial. (5th April 2018) - Hirase, Tatsuya; Kataoka, Hideki; Inokuchi, Shigeru; Nakano, Jiro; Sakamoto, Junya; Okita, Minoru
Abstract : Objective . With the aim of developing a chronic pain prevention program, this randomized controlled trial examined whether exercise training combined with increased physical activity more effectively improves pain and physical activity than exercise training alone in community-dwelling older adults without chronic pain. Methods . We randomized 76 older adults without chronic pain into an intervention groupn = 38 involving exercise training combined with increased physical activity and a control groupn = 38 involving exercise training alone. The exercise training comprised weekly 60-min sessions for 12 weeks. The program to increase physical activity required participants to record their daily step counts using pedometers. Pain intensity, total number of pain sites, and physical activity were assessed before and 12 weeks after the intervention. Results . A time-by-group interaction was found for physical activity, with the intervention group showing significant improvementp < 0.05 . The intervention group also showed greater improvement in pain intensity and total number of pain sites at 12 weeks after intervention than the control groupp < 0.05 . Conclusions . In older adults without chronic pain, exercise training combined with increased physical activity improves key outcome indicators more effectively than exercise training alone. "This trial is registered withUMIN000018503 ."